THE MIDDLE JURASSIC SILICEOUS SEDIMENTARY COVER AT THE TOP OF THE VOURINOS OPHIOLITE (GREECE) - Chiari, Marco; Bortolotti, Valerio; Marcucci, Marta; Photiades, Adonis; Principi, Gianfranco (Ofioliti, 2003)
The age of the Vourinos ophiolitic massif, pertaining to the Jurassic Tethys Ocean, is not yet exactly known. Four sections in the cherts at the top of the basalts yielded well preserved radiolarian assemblages according to which the age of the end of the “ophiolitic activity” (= the end of ocean spreading) was immediately before or within the latest Bajocian interval. A radiometric (Ar/Ar) age of the metamorphic sole at the base of the ophiolite gave 171±4 Ma (late Bajocian), this is, an age slightly older than that of the cherts: this can mean that the metamorphic soles pertain to an intraoceanic hot thrust, doubling the oceanic crust/lithosphere.